Interaksi Sosial Pengajian Online Kitab Turath dalam Membentuk Jiwa Keagamaan Masyarakat Bojonegoro - Zaini Miftah; Taseman; Fahrurrozi (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2022)
This paper reveals the dynamics of the social interaction of online recitation of the turots book in shaping the religious spirit of the community. In this online learning system, it turns out that it is still a magnet in itself in society, even with a wider reach, it can be followed by all levels of the santri community. In